The Clinical Significance of Neuroendocrine Features in Invasive Breast Carcinomas. (16th June 2020) - Lai, Billy Shui‐Wun; Tsang, Julia Y.; Poon, Ivan K.; Shao, Yan; Chan, Siu‐Ki; Tam, Fiona K.; Cheung, Sai‐Yin; Shea, Ka‐Ho; Tse, Gary M.
Abstract: : The latest World Health Organization (WHO) classification categorized invasive breast carcinomas (IBCs) with neuroendocrine (NE) differentiations into neuroendocrine neoplasms (including well‐differentiated neuroendocrine tumor [NET] and poorly differentiated neuroendocrine carcinoma [NEC]) and IBC no special type with NE features (IBC‐NST‐NE). However, little is documented of the clinical significance of this classification; also the precise thresholds and choices of NE markers were variable. In the current study, a large cohort of patients with IBC with NE differentiation were morphologically classified based on the WHO criteria and the clinical relevance of expression of different NE markers (synaptophysin [SYN], chromogranin [CG], and CD56) was evaluated. Among 1, 372 IBCs, 52 NET (3.8%) and 172 IBC‐NST‐NE (12.5%) were identified. Compared with the IBC–no NE cases, NET and IBC‐NST‐NE were similarly associated with positive estrogen receptor (ER) expression and lower grade ( p < .001). For patient outcome, IBC‐NST‐NE, but not NET, demonstrated significantly worse survival than the IBC–no NE cases. Based on high (≥50%) and low (<50%) expression for each NE marker, independent poor disease‐free survival for SYN lo CG lo and SYN hi CG lo cancers (IBC–no NE cases as references, hazard ratio [HR], ≤1.429; p ≤ .026) was found. Interestingly, SYN and CG expression correlated with each other and they shared similar clinicopathologic characteristics; but not with with CD56. In addition, CD56‐only positive cases were associated with hormone receptors negativity and basal markers positivity ( p ≤ .019), and patients' outcome was similar to IBC–no NE cancers. Our findings suggested that NE markers expression may provide information to fine tune treatment strategy. The relevance of CD56 as NE marker requires further studies. Implications for Practice: Invasive breast carcinomas (IBCs) with neuroendocrine (NE) differentiation are heterogeneous in clinicopathologic parameters, biomarker expression, and prognosis. However, there are no specific therapies targeting NE differentiation, and all carcinomas with any NE differentiation are treated similarly as other IBCs. The results of this study suggest that stratification based on NE marker expression levels may provide added prognostically pertinent information, aiding better treatment strategy. In addition, CD56‐only positive carcinomas showed a different clinicopathologic and biomarker expression profile compared with those with chromogranin and synaptophysin expression. Relevance of CD56 as an NE marker requires further studies. Abstract : The prognostic relevance of neuroendocrine differentiation in primary infiltrating breast carcinomas is uncertain. This article evaluates the incidence of carcinoma showing immunohistochemical‐defined neuroendocrine differentiation and the detailed cytomorphologic features, clinicopathologic parameters, and prognosis of these tumors.